A Fourteenth-Century Veronese Sale at the National Library «Sagarriga Visconti Volpi» of Bari (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This paper, after a brief discussion of the recent reorganization of five membranaceous funds of National library «Sagarriga Visconti Volpi» of Bari, reconstructs the history and presents a study (and edition) of the oldest notarial act in the newly-formed collection of parchments reused as chemise bindings (14th-18th century). The document here studied is an instrumentum written by the notary Veronexius – son of Ognibene «de Falsurgo Veron(e)» – dated between 1346 and 1347, and it required further research at funds preserved in the State Archive of Verona; this ancient notarial document, found in Bari during the restoration of an exemplar of the work Delle lettere amorose by Francesco Sansovino, printed in Verona in 1599, allows – among other aspects – continued reflection on patterns of manuscript recycling.DOI 10.17464/9788867743278
Keywords: National library of Bari; membranaceous funds; reused manuscripts; notary Veronexius; State Archive of Verona